2003
DOI: 10.1002/app.13475
|View full text |Cite
|
Sign up to set email alerts
|

Control of particle morphology and film structures of carboxylated poly(methyl methacrylate)/poly (n‐butylacrylate) composite latex particles

Abstract: Particles with a hard core of 66% poly(methyl methacrylate)/34% poly(n‐butyl acrylate) copolymer and a soft shell of pure poly(n‐butyl acrylate) were synthesized via a two‐stage emulsion polymerization process. The particle morphology and the surface structure of the dispersion films were analyzed by atomic force microscopy (AFM). The results, concerning single particle structure and the corresponding films, are correlated to macroscopic properties similar to the minimum expected from the kinetic side. The dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…Computer simulation and microscopic results have shown that film formation of composite particles and the properties of resulting films are influenced by parameters like the T g of the soft and hard phases, the volume fraction of the hard phase (hard/soft phase ratio), and the polymer compatibility between the core and shell. 9 When designed correctly, soft-core/hard-shell particles provide greater film hardness in low VOC paints, because the hard shell reduces the amount of the softer core polymer exposed to the surface. The promise of soft-core/hard-shell latex has led to continued interest in these materials, both in terms of the fundamentals of film formation and also in their application as binders in paint formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulation and microscopic results have shown that film formation of composite particles and the properties of resulting films are influenced by parameters like the T g of the soft and hard phases, the volume fraction of the hard phase (hard/soft phase ratio), and the polymer compatibility between the core and shell. 9 When designed correctly, soft-core/hard-shell particles provide greater film hardness in low VOC paints, because the hard shell reduces the amount of the softer core polymer exposed to the surface. The promise of soft-core/hard-shell latex has led to continued interest in these materials, both in terms of the fundamentals of film formation and also in their application as binders in paint formulations.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain more elastic films, styrene was copolymerized with butyl acrylate (BA), which affords better film formation, owing to the lower glass transition temperature of the resulting PS-co-PBA copolymer. [23] With increasing BA content, the particle size increases from 150 nm for pure PS to 450 nm for PS-co-PBA with 50 wt % PBA. As expected, films derived from the polymer suspensions of PSco-PBA with PS/PBA ratios (w:w) of 70:30 and 60:40 are transparent and more elastic.…”
mentioning
confidence: 98%
“…This may be due in part to the use of two different techniques. From the UNH data it is possible to compare the observed volumetric growth ratio ((D f /D i ) 3 , where D f and D i are the final and seed diameters), to the expected value (taking into account the different polymer densities) because measurements for both the seed and composite latices are available. In the case of system 2, the observed ratio (2.13) is close to that expected (2.2).…”
Section: Appendixmentioning
confidence: 99%